2020
DOI: 10.15171/jhp.2020.09
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gallic acid on rat testopathy following morphine administration: an experimental study

Abstract: Introduction: Morphine (MOR) as a psychoactive agent in the opium family causes free radicals accumulation which leads to failure in spermatogenesis. Gallic acid (GA), a polyphenolic acid, is found in various plants with antioxidant, anti-fungal, anti-viral, and anti-allergic activities. The purpose of this study was to evaluate the effects of GA against MOR-induced damage to the reproductive parameter of rats. Methods: Sixty-four male Wistar rats (8 weeks, 220-250 g) were categorized into 8 groups by random (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Another study showed that utilizing gallic acid in male rats treated with lead acetate reduces the level of MDA in the testis tissue (Bello & Idris, 2018). Gallic acid was found to improve sperm count, motility, viability, morphology, serum testosterone, and total antioxidant levels in male rats given morphine (Jalili et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Another study showed that utilizing gallic acid in male rats treated with lead acetate reduces the level of MDA in the testis tissue (Bello & Idris, 2018). Gallic acid was found to improve sperm count, motility, viability, morphology, serum testosterone, and total antioxidant levels in male rats given morphine (Jalili et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…# p < 0.05 when compared to the cryopreserved control and the 100 μg/ml gallic acid group. The data is presented as the mean ± SEM sperm count, motility, viability, morphology, serum testosterone, and total antioxidant levels in male rats given morphine (Jalili et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations